The Utilization of Colonial Heritage in Tourism Development - Dewa Ayu Diyah Sri Widari (Institut Seni Indonesia Denpasar, 2023)
The purpose of this study was to identify the utilization of colonial heritage as a tourist attraction in the development of tourism. The writing of this article uses a method of data collection through document studies. The use of colonial heritage in several countries raises different views. The understanding of inheritance in general is influenced by a variety of dynamics. The utilization of colonial heritage in the development of tourism in a country raises pros and cons among the local population. On the one hand, it has the view that the uniqueness of colonial heritage can be a tourist attraction aimed at obtaining income for the community and the country. In addition, colonial heritage can also be used as a regional or national identity. But other parties argue, colonial heritage can remind people of the past so that its use can cause unpleasant memories. The economic benefits arising from the development of the tourism sector are an important factor in building preservation decisions and acknowledging colonial heritage has an important role so much effort is made for conservation. Some colonial heritage still survives and reveals the country's history and the identity of its citizens, serving as administrative and business venues as well as tourist attractions.